Effect of Stichopus hermanii extract on interleukin-6 levels in a high-fat diet-induced rat model of inflammation - Diah Purwaningsari; Sihning Endah J. Tehupuring; Nita Pranitasari; Lestari Dewi (Faculty of Pharmacy, Universitas Pancasila, 2026)
Atherosclerosis is a major contributor to cardiovascular diseases and is increasingly recognized as a chronic low-grade inflammatory disorder involving oxidative stress and immune-mediated mechanisms. Interleukin-6 (IL-6) is a key proinflammatory cytokine that links oxidative stress and immune responses and has been widely associated with the progression of inflammation-related vascular conditions and the acceleration of atherosclerosis. The adverse effects of current pharmaceuticals have driven interest in herbal alternatives with fewer side effects. Sea cucumbers are recognized as potent biomedical resources with bioactivities against atherosclerotic pathways. This study aimed to identify the effects of Stichopus hermanii extract on IL-6 levels in a rat model of atherosclerosis induced by a high-fat diet. An experimental in vivo study utilizing a post-test-only control group design was performed on 32 Wistar rats, categorized into four groups: negative control (standard diet), positive control (high-fat diet), and two treatment groups administered Stichopus hermanii extract at dosages of 35 mg and 40 mg per 200 g body weight. IL-6 concentrations were markedly increased in rats subjected to a high-fat diet compared to those in the conventional diet group (p<0.05). Stichopus hermanii extract at both dosages markedly diminished IL-6 concentrations compared to the positive control group. The 40 mg dose reinstated IL-6 levels to those similar to the negative control group, signifying a dose-dependent anti-inflammatory effect. The extract of Stichopus hermanii successfully regulated IL-6 levels in rats with atherosclerosis induced by a high-fat diet, indicating its potential as a natural anti-inflammatory and cardioprotective agent for managing atherosclerosis.